Performance of justice in Argentina. AHP ratings model - Curchod, Miguel Ángel; Alberto, Catalina Lucía (2022)
Fil: Curchod, Miguel Ángel. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.